A comprehensive Mendelian randomization study highlights the relationship between psychiatric disorders and non-tumor gastrointestinal diseases - Liang, Xiru; Huang, Xindi; Cheng, Yutong; Wang, Ziwei; Song, Yahua; Shu, Qiuai; Xie, Ning (Frontiers in Genetics, 2024)
Objective: Previous observational studies revealed the potential correlation between psychiatric disorders (PDs) and non-tumor gastrointestinal diseases (NTGDs).However, their causation remains unclear. Methods: We explored the causal relationship between PDs and NTGDs through bidirectional two-sample Mendelian randomization (MR) study. Large-scale genome-wide association study (GWAS) summary statistics and bidirectional two-sample MR study were used to assess the causality between PDs and NTGDs. Multiple sensitivity analyses were used to identify the robustness of our results. Results: We found that major depression was causally associated with increased risk of gastric ulcer (OR: 1.812, 95% CI: 1.320-2.487, P < 0.001) and irritable bowel syndrome (OR: 1.645, 95% CI: 1.291-2.097, P < 0.001).Meanwhile, genetically predicted gastroesophageal reflux disease contributed to the increased risk of anxiety disorders (OR: 1.425, 95% CI: 1.295-1.568, P＜0.001), and ulcerative colitis was related to increased risk of attention deficit/hyperactivity disorder (OR: 1.042, 95% CI: 1.008-1.078, P = 0.0157). Conclusions: Our study provided MR evidence to support the close causality and identify the specific direction between eight PDs and eight common NTGDs. Experimental studies to further examine the causality, underlying mechanism, and therapeutic potential of PDs and NTGDs are required.